PENGARUH NILAI KEPERCAYAAN MONIBI SEBAGAI PEMBENTUK STRUKTUR DASAR TATA RUANG PUSAT PERMUKIMAN DI KOTA KOTAMOBAGU - Ointu, Afni; Sudaryono, Sudaryono (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
This research explains that a belief that lives and is believed by the community can be the basic structure of the spatial formation of a settlement center. As one of the cities in North Sulawesi Province, Kotamobagu City is synonymous with the history and culture of the Bolaang Mongondow tribe. The attachment to the Bolaang Mongondow culture can also be seen from the community's unique settlement tradition because it has uniformity and consistency of space for government functions, schools, mosques and fields in one area located in settlement centers. This can be found in 16 villages and sub-districts in Kotamobagu City. This unique phenomenon was investigated more deeply using the inductive-qualitative-phenomenological method, which found that the monibi belief value is the basis for forming the basic spatial structure of the settlement center with a classification consisting of spiritual space and open space. The simultaneous relationship between spiritual space and open space centered in the same landscape gives birth to a settlement center at the central point of the settlement space. The basic spatial structure formed through the monibi belief value has crossed the passage of time with different actors but its spatial manifestation can still be maintained today not only at the micro scale of the settlement center but also can be identified at the macro scale, namely the city service center of Kotamobagu.